Implementasi Media E-Learning dalam Meningkatkan Belajar Siswa di MAN I Mempawah - Kholilurrahim (LP3M IAI Al-Qolam Malang, 2020)
Here the researcher will describe the keywords related to this research. First, implementation can simply mean an application or implementation in a goal. In addition, implementation is also interpreted as an evaluation material, on the other hand implementation can also be interpreted as the expansion of activities that are mutually adapting between one activity and another, from the definitions above it can be concluded that implementation is leading to activity, action, or mechanism of a system. The expression mechanism implies that implementation is not just an activity, but an activity that is planned and carried out in earnest based on the reference to certain norms to achieve the objectives of the activity. Second, e-learning media is a learning tool prepared by formal educational institutions at this time which aims to facilitate students' online learning with teachers, e-learning media is the first media used by MAN I Mempawah which is used by the school during the situation that makes it impossible to do face-to-face learning during COVID19 situation. Third, learning in context of cognitive theory is a process that emphasizes the learning process rather than student learning outcomes. Learning is a change perception and understanding which is not always visible as visible behavior. From the explanation of the three key words above, a conclusion can be drawn between Implementation, E-Learning Media and Learning which is one unit that cannot be separated to get a concrete conclusion in a study conducted by the researcher. There are three expectations that the researcher wants to know (1). How to implement or students' learning implementation at MAN I Mempawah in academic year of 2020/2021, (2). What are the benefits of using e-learning media used by MAN I Mempawah students' in academic year of 2020/2021. Keywords: Implementation, E-Learning media, Learning.